Location-Dependent Signaling of the Group 1 Metabotropic Glutamate Receptor mGlu5 - Jong, Yuh-Jiin I. (Mol Pharmacol, 2014)
Although G protein–coupled receptors are primarily known for converting extracellular signals into intracellular responses, some receptors, such as the group 1 metabotropic glutamate receptor, mGlu5, are also localized on intracellular membranes where they can mediate both overlapping and unique signaling effects. Thus, besides “ligand bias,” whereby a receptor’s signaling modality can shift from G protein dependence to independence, canonical mGlu5 receptor signaling can also be influenced by “location bias” (i.e., the particular membrane and/or cell type from which it signals). Because mGlu5 receptors play important roles in both normal development and in disorders such as Fragile X syndrome, autism, epilepsy, addiction, anxiety, schizophrenia, pain, dyskinesias, and melanoma, a large number of drugs are being developed to allosterically target this receptor. Therefore, it is critical to understand how such drugs might be affecting mGlu5 receptor function on different membranes and in different brain regions. Further elucidation of the site(s) of action of these drugs may determine which signal pathways mediate therapeutic efficacy.